Economic Performance Over the Conflict Cycle - Staines, Nicholas (IMF Working Papers; Working Paper ;, 2004)
The paper finds a significant shift in the economic characteristics of civil conflicts during the1990s. Conflicts have become shorter but with more severe contractions and a stronger recovery of growth. The overall length and cost of the conflict cycle has probably declined. The stance of macroeconomic policy was an important factor while the underlying "conflict process" remained unchanged. This shift seems related to changes in aid flows since the Cold War: donors became disinclined to provide support during conflict, but more inclined after conflict. These findings are buttressed by the post-conflict experience of countries that received financial assistance from the IMF and of the Democratic Republic of Congo (DRC). These findings have implications for policy and aid priorities after conflict.